A preliminary study on teachers' awareness and knowledge of speech-language therapy in Kota Bharu, Kelantan - Affizal Ahmad,; Malarvini Vesualingam,; Mohd Normani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Speech-language therapists (SLTs) are experienced in recognising the symptoms and signs of speech-language disorders and can help the afflicted children overcome those disorders with appropriate intervention. Furthermore, with the increase in the number of children with special educational needs, teachers are expected to identify students with speech-language disorders, which is also a shared responsibility of SLTs. However, the teachers’ awareness and knowledge of speech-language therapy are relatively unknown. Therefore, this study aimed to identify the primary school teachers' awareness and knowledge of speech-language therapy services in Kota Bharu, Kelantan. A total of 105 primary school teachers participated in this survey-based study. The findings discovered that the teachers' awareness and knowledge were limited. Among the participants, only 25.7% indicated a high awareness and knowledge regarding the SLTs' roles, yet 68.6% of the teachers had never read about speech-language therapy, and 63.8% had never heard anything about SLPs previously. Consequently, more emphasis on awareness and knowledge of SLPs should be executed for schoolteachers. This will assist the schoolteachers in identifying children with special needs in need of SLT services in the future.